The historic timber structure conservation of Madrasah Idrisiah Building, Kuala Kangsar, Perak / Afzanizam Muhammad, Siti Norlizaiha Harun and Mohd Nurfaisal Baharuddin - Muhammad, Afzanizam; Harun, Siti Norlizaiha; Baharuddin, Mohd Nurfaisal (2018)
Madrasah Idrisiah is the first royal religious School in Perak. The main building is a double storey timber structure and was built in the year 1917. In 2017, through the allocation from the National Heritage Department of Malaysia, the main building of the Madrasah Idrisiah has undergone building conservation works. The building has a timber structure defect such as deterioration due to moisture problems, insect attack, fungal attack, and improper repair works. The conservation of timber structures involves the repair of beams, column, shafts and roof structures of the mosque. This paper discusses the methods and techniques for conservation work on a historic timber structure which involves the main block of Madrasah Idrisiah. The proposed conservation method is the minimal intervention and the main aims are to restore and consolidate the existing timber structure. The proposed conservation method used is based on historic building conservation guideline by Malaysia National Heritage Department.